2021
DOI: 10.1111/beer.12343
|View full text |Cite
|
Sign up to set email alerts
|

Making implicit CSR explicit? Considering the continuity of Japanese “micro moral unity”

Abstract: While there are many studies that address how well Japanese companies have adopted explicit CSR practices, our understanding of their own views on such practices is still limited, particularly of the difference in their views before and after the process of making implicit CSR explicit. The present research thus aims to address this apparent change by providing comparative case studies of two Japanese companies selected from two different time periods. The findings indicate there is a continuity observable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The theoretical significance of this study is that it provides new knowledge regarding sustainability and sustainability reporting by showing that not only the adoption of IR but also the promotion of integrated thinking is necessary to change organisational values towards the creation of long‐term value, especially when Japanese companies' consideration of the long‐term view is doubtful (Horiguchi, 2021). In terms of practical significance, this study specifically contributes to new knowledge about how IR can be applied effectively in companies in countries with a similar IR situation as Japan, by showing the changes brought by IR adoption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical significance of this study is that it provides new knowledge regarding sustainability and sustainability reporting by showing that not only the adoption of IR but also the promotion of integrated thinking is necessary to change organisational values towards the creation of long‐term value, especially when Japanese companies' consideration of the long‐term view is doubtful (Horiguchi, 2021). In terms of practical significance, this study specifically contributes to new knowledge about how IR can be applied effectively in companies in countries with a similar IR situation as Japan, by showing the changes brought by IR adoption.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the purpose of this study is to investigate the approaches and internal mechanisms that companies employ in their application of IR and to examine whether IR drives organisational change at an early stage through a multiple case study. In Japan, ‘ethically questionable practices have been going on behind the explicitly articulated CSR policies’ (Horiguchi, 2021, p. 311), while some studies have shown large Japanese companies integrating their long‐term perspectives into their relationship with stakeholders (Eweje & Sakaki, 2015; Fukukawa & Moon, 2004; Hosoda & Suzuki, 2015). IR can be just a way of storytelling (Higgins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant as CEOs have been perceived as important actors to explain corporate social behaviour (Karassin and Bar-Haim, 2016; Saha et al , 2019; Yin et al , 2016). Second, it offers an understanding of what CSR means in specific societies, complementing previous research that links CSR actions and cultural and social norms (Cahan et al , 2017; Horiguchi, 2021). Finally, it suggests that the way CSR is perceived by corporate executives depends on the national settings in which the firm operates as illustrated by prior studies such as Carson et al (2015), Vallentin (2015) and Horiguchi (2022).…”
Section: Introductionmentioning
confidence: 90%
“…However, a consideration of the nature of social sustainability practices of large-scale mining companies raises questions of the intentions of corporate managers and the intrinsic qualities of their actions. As Horiguchi (2021) has observed, corporate managers may engage in unethical practices behind explicitly articulated sustainability policies. As such, it is not merely the explicit social sustainability strategies of firms that are important, but also the mindset of managers to internalise their social costs and engage in activities that genuinely reflect the moral basis of ethical decisions.…”
Section: Implications For Theory Policy and Ethicsmentioning
confidence: 99%